New insight into hybridization and unidirectional introgression between Ammodytes japonicus and Ammodytes heian (Trachiniformes, Ammodytidae). - Jin-Koo Kim; Seung Eun Bae; Soo Jeong Lee; Moon Geun Yoon (PLoS ONE)
Based on northern (NOL) and southern (SOL) mitochondrial lineages, recently, it proposed the new species Ammodytes heian and revived the species name Ammodytes japonicus to describe sand lances from the northwestern Pacific Ocean. This study used molecular methods to investigate genetic relationships between the two sand lance species in Korea and Japan. In total, 154 specimens were collected from four locations in Korea (Baengnyeongdo in the Yellow Sea, Tongyeong in the Korean Strait, and Jumunjin and Gijang in the East Sea), and 50 specimens were collected from a single location in Japan (Wakkanai in the Okhotsk Sea). Mitochondrial DNA analysis demonstrated that the individuals from Baengnyeongdo and Tongyeong all belonged to the SOL, whereas those from Gijang, Jumunjin, and Wakkanai included individuals from both the NOL and SOL (over 75% NOL). Population structure analyses were performed on the same individuals using seven microsatellite DNA markers. The population structure analysis based on 201 specimens identified two clusters (named as northern group and southern group), with the admixture proportion (q) of < 0.1 for the northern group in the Backyeongdo and Tongyeong sand lances and < 0.1 for the southern group in the Wakkanai sand lances. The high heterogeneity indicated that the former was probably A. japonicus and the latter probably A. heian. However, the admixture proportion in the Jumunjin and Gijang sand lances was 0.71-0.75 for the southern group, indicating that hybridization and unidirectional introgression from SOL to NOL occurs in southwestern margin of the East Sea. Our findings illustrate the speciation process based on different patterns of gene flow between Korean and Japanese sand lance, which is strongly influenced by both the paleo-climatic change and the contemporary local oceanic current pattern.